Avatar as a Self-Representation: Analysis of Digital Identity Formation in the Online Game Roblox - Rika Wulandari; Masyuri Masyuri (Lembaga Yasin AlSys, 2026)
The rapid development of digital technology and online game platforms such as Roblox has intensified scholarly attention to how users construct and express digital identity through avatar customization. This study aims to analyze avatars as forms of self-representation among active Roblox users in virtual environments. A qualitative descriptive approach was employed, with data collected through an online Google Forms survey consisting of open-ended questions about users’ experiences in creating and modifying avatars. The data were analyzed using a descriptive thematic approach to identify recurring patterns of meaning. The findings show that avatars are understood through four main dimensions: similarity to the real self, representation of the ideal self, symbolic expression of identity, and behavioral transformation. Avatars not only reflect users’ actual self-perceptions but also function as media for projecting idealized identities through selected visual symbols. In addition, avatar characteristics may influence users’ self-confidence and behavior during virtual interactions. The study concludes that avatars in Roblox serve as spaces for negotiating digital identity within virtual environments. These findings contribute to a broader understanding of the psychosocial role of online game platforms in the identity development of young digital users and highlight the importance of designing virtual spaces that support healthy, authentic, and inclusive self-expression.